Homeopathy in the Treatment of Dermatitis Herpetiformis—A Case Presentation - Nwabudike, Lawrence C. (Homœopathic Links, 2015)
Dermatitis herpetiformis (DH) is a chronic bullous disease thought to be the consequence of an immune reaction in the skin. There are strong associations with gluten-sensitive enteropathy (GSE) and the elimination of gluten from the diet has been shown to improve the disease. Various treatment modalities are available for the suppression of the clinical manifestations of the disease, including the elimination of gluten-containing foods, dapsone, colchicine, azathioprine and prednisolone. A case of histopathologically confirmed DH, successfully treated with homeopathy, is presented. The homeopathic medicine Aurum metallicum at MK potency was used.
Keywords: Dermatitis herpetiformis; Duhring disease; Gluten-sensitive enteropathy; Immunoglobulin A; Bullous dermatosis; Aurum metallicum; Rhus toxicodendron